Comment les coachs individualisent les maux du travail - Anne Jourdain (La Nouvelle Revue du Travail)
Over the past few years, a market for career change coaching has been developing alongside the professional training field. This market has been taken over by independent coaches who offer to support professionally dissatisfied executives. They help them discover their “hidden talents” and create their “dream job” Based on an analysis of the coaches’ discourse (social networks, media, interviews…), the article shows how the development of career transition coaching is contributing to the individualization and depoliticization of working relationships. The psychologization of their support, in the absence of labour market expertise, encourages them to favour individual “exit” over collective “voice”.